Knowledge, Attitude and Practice on COVID During the COVID-19 Pandemic: A Systematic Review - Singh, Ajanta; Ranjitkar, Uma Devi; Singh, Shreejana (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Corona virus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. The World Health Organization (WHO) declared the novel corona virus outbreak a global pandemic on March 11 2020 due to its rapid spread on a global scale. Now the world is in the midst of COVID-19 pandemic. More than 157289118 cases have been reported in 222 countries and mortality has reached a total of 3277272. The best way to prevent and slow down transmission is to be well informed about COVID-19 virus, the disease its causes and how it spreads. Adequate knowledge, positive attitude and good practice are the only key to control the pandemic. This review aims to study the present level of knowledge, attitude and practice done among respondents in various countries. Methods: The review presents a summary of studies done on knowledge, attitude and practice during COVID-19 pandemic among the primary level students, graduate and post graduate students and the general population. Research articles were accessed through online search from November 2020 to April 2021. Collected articles were reviewed and conclusions were drawn in terms of knowledge score, attitude score and the level of practice. Results: The study population were from China, Nepal, India, Iraq, Bangladesh, Palestine, Nigeria, and Egypt. The population of study varies from primary level students to post graduate university level students and most of the studies were done on general population. Among the studies knowledge score ranged from minimum 48.3% in Bangladesh to highest 99.5% in Nigeria where knowledge was gained mainly through social media and television. The attitude score ranged from minimum 4.54 + 1.76 (Range 0 - 8) in Wuhan, China to maximum 79.5% in Nigeria. Similarly, the practice score ranged from 51.6% in Bangladesh to 87.9% in China. Conclusions: Analysis reveals that the level of knowledge was average, have positive attitude and good practices. Utility of knowledge and positive attitudes and application of knowledge into practice will hopefully can control the spread of COVID-19. Key Words: Attitude; Knowledge; Practice; Review